A manual reduction of hernia under analgesia/sedation (Taxis) in the acute inguinal hernia: a useful technique in COVID-19 times to reduce the need for emergency surgery-a literature review - East, B; Pawlak, M; de Beaux, A C (Hernia, 2020)
BACKGROUND: Acute IH is a common surgical presentation. Despite new guidelines being published recently, a number of important questions remained unanswered including the role of taxis, as initial non-operative management. This is particularly relevant now due to the possibility of a lack of immediate surgical care as a result of COVID-19. The aim of this review is to assess the role of taxis in the management of emergency inguinal hernias. METHODS: A review of the literature was undertaken. Available literature published until March 2019 was obtained and reviewed. 32,021 papers were identified, only 9 were of sufficient value to be used. RESULTS: There was a large discrepancy in the terminology of incarcerated/strangulated used. Taxis can be safely attempted early after the onset of symptoms and is effective in about 70% of patients. The possibility of reduction en-mass should be kept in mind. Definitive surgery to repair the hernia can be delayed by weeks until such time as surgery can be safely arranged. CONCLUSIONS: The use of taxis in emergency inguinal hernia is a useful first line of treatment in areas or situations where surgical care is not immediately available, including the COVID-19 pandemic. Emergency surgery remains the mainstay of management in the strangulated hernia setting.
Keywords: pandemie; COVID-19; inguinální hernie; konzervativní terapie; Humans; Betacoronavirus; urgentní zdravotnické služby; Hernia, Inguinal; Emergency Medical Services; Health Services Accessibility; Conservative Treatment; operace kýly; virová pneumonie; dostupnost zdravotnických služeb; Clinical Decision-Making; Musculoskeletal Manipulations; kontrola infekce; klinické rozhodování; koronavirové infekce; Coronavirus Infections; Time-to-Treatment; čas zasáhnout při rozvinutí nemoci; Infection Control; lidé; Herniorrhaphy; SARS-CoV-2; Pandemics; Pneumonia, Viral; muskuloskeletální manipulace